1994
DOI: 10.1128/aac.38.2.300
|View full text |Cite
|
Sign up to set email alerts
|

Amphotericin B incorporated into egg lecithin-bile salt mixed micelles: molecular and cellular aspects relevant to therapeutic efficacy in experimental mycoses

Abstract: The cellular activities of amphotericin B (AmB) used as Fungizone were compared with those of AmB complexed to either egg lecithin and glycocholate (Egam) or egg lecithin and deoxycholate (Edam). Under conditions in which leakage of K+ from erythrocytes and cultured L cells treated with Fungizone was almost complete, Egam and Edam containing concentrations of AmB severalfold greater than the concentration of AmB in Fungizone had no effect but retained the ability to decrease the level of retention of K+ in fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…The second possible reason for the differences in the relative therapeutic efficacies of Fungizone and Egam is linked to our finding that Egam is more stable than Fungizone in the presence of serum lipoprotein (5). It can be assumed that Egam stays in blood longer and is scavenged more effectively by cells of the reticuloendothelial system than the AmB which has dissociated from Fungizone.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The second possible reason for the differences in the relative therapeutic efficacies of Fungizone and Egam is linked to our finding that Egam is more stable than Fungizone in the presence of serum lipoprotein (5). It can be assumed that Egam stays in blood longer and is scavenged more effectively by cells of the reticuloendothelial system than the AmB which has dissociated from Fungizone.…”
Section: Resultsmentioning
confidence: 83%
“…Here we report a comparison of the therapeutic efficacies of these formulations and Fungizone in the treatment of murine models of candidiasis and cryptococcosis. In the accompanying report (5) we consider the molecular and cellular aspects of the therapeutic activities of these formulations.…”
mentioning
confidence: 99%
“…However, its narrow therapeutic index and adverse side effects, especially nephrotoxicity, limit its use (8,34,35). Numerous researchers have tried over the last two decades to overcome AMB toxicity problems and improve the safety of the drug by formulating AMB into lipid-based delivery systems (2,9,18,20,25,33,36,39,40,42). Different lipid-based AMB systems were developed, including AMBisome, Amphotec, and Abelcet, which improve AMB's therapeutic drug index (22).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, some work has concluded that the particle size has an influence on toxicity (3,17,22) and on the activity of this drug for the treatment of different diseases (6,7,14,31). Therefore, it is probable that the molecular disposition of AMB could account for the different activities, toxicities, and pharmacokinetics observed.…”
Section: Discussionmentioning
confidence: 99%
“…The absorption spectrum of the AMB microspheres presented maxima at 420, 392, 370, and 358 nm. This conformation would correspond to associated or aggregated molecules, as indicated in previous work (6). The absorption spectrum of AMB-Doc showed only one important peak, at 328 nm, indicating the prevalence of a different molecular disposition, probably oligomeric water-soluble AMB (22).…”
Section: Physicochemical Characterization Of Amb Formulationsmentioning
confidence: 98%